Optimizing the Cutting Time and Surface Finish for EDMWire Cut Process of AISI 1045 Steel - Nur, Rusdi; M, Muas; Risal, Syah (Politeknik Negeri Ujung Pandang, 2018)
This paper aims to optimize the machinedsurface as well as to study the effect of current strength andwire speed on wire cut machining on AISI 1045 steel againstthe timing of roughness of straight gear surface. The surfaceresults analyzed are the surface roughness values obtained byconducting surface roughness testing. Variations of currentused are 3 amperes, 5 amperes, and 7 amperes, while the wirespeed used is 8mm / min, 10 mm, min, and 12 mm / min. In theprocess of wire cut machining is used a brass cutting materialwith 0.25 mm wire diameter. The results showed that thegreater the current and wire speed used then the surfaceroughness value will be lower, otherwise the smaller currentand wire speed used then the surface roughness value will behigher. The results of data analysis using ANOVA analysis,correlation, and regression method obtained optimal conditionto get low surface roughness value and fast cut time that is at 7amperes current with wire speed 8 mm / min.